Determination of Alkyl Esters Content in PDO Extra Virgin Olive Oils from Sicily - Rosaria Costa; Giovanni Bartolomeo; Emanuele Saija; Rossana Rando; Ambrogina Albergamo; Giacomo Dugo (Journal of Food Quality)
The quality parameter of alkyl esters of fatty acids was checked in a variety of Italian olive oil samples. In particular, 34 samples of extra virgin olive oils (EVOOs) from South Italy (Sicilian orchards), produced in the years 2014-2015, have been subjected to the analytical protocol dictated by the European Union for the determination of alkyl esters, as an indicator of oil’s quality. All the samples analyzed resulted to be well below the limit set by EU Directive. Besides recently produced EVOOs, a set of very aged oils, produced in the years 1996–2000, were analyzed as well. The main finding was that alkyl esters increased in correspondence with deterioration processes.